Pengaruh Beban Kerja dan Disiplin Kerja Terhadap Intensi Turnover Karyawan YANIIBS, Parung - Bogor: turnover - idrus idrus (Al Ashriyyah, 2018)
Abstract. Every organization wants its employees to have a high ability to work discipline, and retain employes. High turnover rate which will cause negative impact to the organization , it is like creating instability and uncertainty of the condition of labor , the organization also lost experienced employees who have been getting a lot of training and ultimately need to retrain new employees. The purpose of this research is to examine and analyze the effect of work load and work discipline on turnover intention. Sampling method using all population. The data is taken directly using a questionnaire with 120 respondents employees at YANIIBS Parung-Bogor. The method of analysis used in this research is multiple linear regression, analysis of data using SPSS software. Workload and discipline with the same affect turnover intention by 56.2% and 43.8% is explained by other variables. Research shows work load and work discipline togather significantly influence turnover intention. This means that variable turnover intention (Y) can be explained by the two independent variables work load (X1) and disciplin (X2). The results of analysis, showed that work load and discipline is a possitive significant effect on turnover intention. Work load variables are variables that most influence on turnover intention,also stated that increased workload contributed toincreasing turnover intention.